Alien hotspot: Benthic marine species introduced in the Brazilian semiarid coast. (January 2022) - Soares, Marcelo Oliveira; Xavier, Francisco Rafael de Lima; Dias, Nalu Maia; Silva, Maiara Queiroz Monteiro da; Lima, Jadson Pinto de; Barroso, Cristiane Xerez; Vieira, Leandro Manzoni; Paiva, Sandra Vieira; Matthews-Cascon, Helena; Bezerra, Luís Ernesto Arruda; Oliveira-Filho, Ronaldo Ruy; Salani, Sula; et al.
Abstract: In this study, we provide a baseline assessment of introduced marine species along the extensive ( 600 km) Brazilian semiarid coast. We reported 27 introduced and 26 cryptogenic species. Moreover, the main vectors of introduction were ballast water, shipping lines, oil and gas activities, biofouling, and rafting on plastic debris. The taxa were Ascidiacea (17 species) and Bryozoa (17), followed by Crustacea (6), Mollusca (6), Cnidaria (3), Echinodermata (3), and Porifera (1). Among these invertebrates, some species are recognized as drivers of impacts such as the invasive corals ( Tubastraea tagusensis and Tubastraea coccinea ), the bivalves Isognomom bicolor and Perna viridis, the crab Charybdis hellerii, the brittle star Ophiothela mirabilis, and, finally, the bryozoan Membraniporopsis tubigera . These species threaten the biodiversity of unique ecosystems such as intertidal sandstone reefs, shallow-water coral reefs, and mesophotic ecosystems. Moreover, the up-to-date results highlight that this region is a hotspot of bioinvasion in the tropical South Atlantic. Graphical abstract: Unlabelled Image Highlights: A baseline assessment study compiling information from different taxonomic groups We reported 27 introduced and 26 cryptogenic species Ballast water and biofouling were the main forms of species introduction in this low-latitude area. Artificial habitats constitute a network of stepping-stone habitats for range expansion.